MEKANISME GCG, LEVERAGE, PROFITABILITAS, TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2016 – 2018 - Titik Dwiyani; Purnomo (Media Akuntansi, 2020)
Research entitled "Mecanisme GCG, Leverage, ROA on Tax Avoidance " on manufacturing companies listed on the Indonesia Stock Exchange in the period 2016 - 2018 aims to determine the effect of GCG, Leverage, ROA on Tax Avoidance . Proxies used are Kom-I, Kom-A, Kep-I,DAR, ROA, and Tax Avoidance. The population and research sample are manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018 using the stratified purposive sampling method. Based on these methods 37 companies were obtained that could be used as research samples. Analysis of research data using multiple linear regression were analyzed using SPSS. The partial analysis test results show the results of GCG affect to Tax Avoidance and Leverage, ROA not affect Tax Avoidance.